BCR/ABL1-negative, triple-negative, myeloproliferative neoplasm with a hitherto undescribed, isolated, SH2B3 (LNK) gene mutation: A case report - Emily Feldpausch; Shilpa Sambidi; Durga Cherukuri; Jagmohan Sidhu (Elsevier, 2018)
The myeloproliferative neoplasms (MPNs) are chronic myeloid cancers (clonal hematopoietic disorders) that are characterized by the overproduction of terminally differentiated (mature) blood cells, and that may evolve into acute myeloid leukemia (AML). The literature indicates that three known driver mutations currently exist in BCR/ABL1-negative MPNs: JAK2, MPL and CALR. A small percentage of BCR/ABL1-negative MPN cases lack mutations in all three of these genes and are thus referred to as triple- negative. This case report is of a 48-year-old female with non-chronic myeloid leukemia (non-CML) MPN with increases in all three cell lineages in the bone marrow. No abnormalities were detected in chromosome analysis and FISH studies. Her myeloid molecular profile analyzed by targeted next generation sequencing (NGS) found a frameshift mutation in the SH2B3 (LNK) gene, but no mutations in any other genes typically mutated in MPNs. A few other cases of triple-negative, non-CML MPNs with SH2B3 (LNK) gene mutations have been reported, but we are adding a case of an MPN with a hitherto undescribed frameshift SH2B3 (LNK) mutation between the DD and PH domains of the gene. Currently, the literature is not clear whether SH2B3 (LNK) mutation is a driver mutation or not. More investigation is needed to clarify the significance of SH2B3 (LNK) gene mutations especially in the pathogenesis of MPNs lacking major driver gene alterations. Keywords: Myeloproliferative neoplasm, SH2B3 (LNK) mutation, JAK2 mutation, CALR mutation, MPL mutation